A teologia como instrumento de subjetividade psíquica na formação do sujeito - Martins, Fabiano Battemarco da Silva; Mildenberg, Emerson Cláudio (Revista Terra & Cultura: Cadernos de Ensino e Pesquisa; Vol 41 No 78 (2025): Publicação Contínua, 2025)
This article is a literature review of the religious phenomenon. It aims to understand the relationship between faith and psychic well-being from the perspective of a psychoanalytic analysis. More specifically, it seeks to analyze the occurrences of empowerment among individuals who follow a religious faith and to point out the mechanisms and processes that lead to the production of subjectivity through the experience of religious faith. To this end, the study discusses three main themes, which are: empowerment, the concept of animism, and the concept of individual and group projection, which in turn allows itself to be used by religion. In our review, it was found that empowerment allows man autonomy, providing him with mechanisms to produce a certain power for the religious individual. Animism consists of religious ideas and practices based on the idea of soul and spirit with a tendency to give life to inanimate beings. And finally, projection, allows man to drain from himself, Through thought, all undesirable feelings, and through compulsions, as something compensatory, relieve your guilt.